Computational Geometry-Based 3D Yarn Path Modeling of Wound SiCf/SiC-Cladding Tubes and Its Application to Meso-Scale Finite Element Model - Tang, Jianbo; Zhao, Gang; Wang, Jun; Ding, Yue; Feng, Yajie; Chen, Yunsheng; Zhang, Chao; Huang, Qing; Xin, Shiqing; Xu, Jian (Frontiers in Materials, 2021)
Filament winding process is a competitive performing technology for nuclear fuel cladding due to its high automation. The study of yarn path on the mandrel surface is vital in order to design and produce the cladding with the desired mechanical properties, reducing manufacturing times and costs. The geodesic and semi-geodesic trajectories are applied to create a 3D yarn path in this paper. A 3D yarn path optimization method based on the principle of minimum potential energy was proposed to simulate overlapping effect in accord with the real winding process. The finite element (FE) mesh based on the 3D yarn path has been used for the mechanical analysis of the cladding. The embedded region constraint is used to define the interaction between the matrix mesh and the yarn mesh. Based on the meso-scale FE model, the mechanical behavior of the wound SiCf/SiC nuclear fuel cladding tube is studied in detail, which demonstrates the superiorities over the traditional macro laminate model.